2018
DOI: 10.1111/jre.12545
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine inhibits osteogenic differentiation of human periodontal ligament cells under cyclic tensile stress through canonical Wnt pathway and α7 nicotinic acetylcholine receptor

Abstract: These results indicate that nicotine prevents the increased osteogenic potential of hPDLCs induced by cyclic tensile stress by binding to an α7 nicotinic acetylcholine receptor and activating the canonical Wnt pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Most recently, in-vitro cell type verification was increasingly used including several studies on hPDLCs (Marchesan et al, 2011), that were also reported in some of the included studies herein, i.e. flow cytometric analysis of cell surface markers (Wang H. et al, 2019;Wu et al, 2019a), osteogenic potential as reflected by ALP staining and/or Ca 2+ deposition (Jacobs et al, 2018;Wang H. et al, 2019), cell type specific gene expression pattern (Memmert et al, 2019), and immunohistochemical staining of vimentin and cytokeratin (Sun et al, 2017;Yu et al, 2018;.…”
Section: Reasons For Heterogeneity Of Genes/proteins/ Metabolites Regulationmentioning
confidence: 99%
“…Most recently, in-vitro cell type verification was increasingly used including several studies on hPDLCs (Marchesan et al, 2011), that were also reported in some of the included studies herein, i.e. flow cytometric analysis of cell surface markers (Wang H. et al, 2019;Wu et al, 2019a), osteogenic potential as reflected by ALP staining and/or Ca 2+ deposition (Jacobs et al, 2018;Wang H. et al, 2019), cell type specific gene expression pattern (Memmert et al, 2019), and immunohistochemical staining of vimentin and cytokeratin (Sun et al, 2017;Yu et al, 2018;.…”
Section: Reasons For Heterogeneity Of Genes/proteins/ Metabolites Regulationmentioning
confidence: 99%
“…Consistent with our findings, many authors have noticed that α7nAChR is closely associated with an enhanced proliferative property of various cells, including normal cells, cancerous cells ( 13 , 17 ), and stem cells ( 30 32 ). On the contrary, activation of α7nAChR results in a reduction of proliferation in adipose-derived stem cells ( 12 ), inhibited osteogenic differentiation in human periodontal ligament cells ( 33 ), chondrogenic differentiation in bone mesenchymal stem cells ( 34 ), and inhibited proliferation and differentiation in osteoblasts ( 35 ). Inconsistently, it has been reported that selective activation of α7nAChR causes a limited proliferation but promotes the differentiation of basal epithelial cells in airway regeneration ( 21 ) and of neural stem cells after stroke ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The key to regeneration of periodontal tissues is the proliferation and migration of residual periodontal ligament cells, and differentiation into osteoblasts and cementoblasts. hPDLFs are the major cellular component required for the development and function of periodontal tissues (30,31). hPDLFs have various functions, including chemotaxis, hyperplasia, adhesion, differentiation into cementoblasts and osteoblasts, and mineralized tissue formation.…”
Section: Discussionmentioning
confidence: 99%